Temporal trends in malignancy incidence and outcomes among kidney transplantation recipients: a multi-center real-world evidence study using the TriNetX network (2000–2010 vs. 2010–2021) - Lai, Gu-Shun; Li, Jian-Ri; Chen, Chuan-Shu; Wang, Shian-Shiang; Lin, Chia-Yen; Yang, Che-Jui; Ho, Hao-Chung; Hung, Sheng-Chun; Chiu, Kun-Yuan; Yang, Cheng-Kuang (Frontiers in Immunology, 2025)
AbbreviationsBMI, body mass index; CI, confidence interval; ESRD, end stage renal disease; HR, hazard ratio; IRB, Institutional Review Board; ICD, International Classification of Diseases; KTX, kidney transplantation; mTOR, mammalian target of rapamycin; PSM, propensity scoring matching; PTM: post-transplantation malignancy; SIR, standardized incidence ratio; SMR, standardized mortality rate.ObjectiveMalignancy is a main cause of mortality and morbidity in kidney transplantation recipients. Advancements in cancer surveillance and treatment may contribute to increased incidence and improved clinical outcomes. This study aimed to investigate the trends and clinical outcomes of post-transplantation malignancies over the past two decades.MethodsWe conducted a retrospective cohort study using the TriNetX network. Common post-transplantation malignancies were identified, and outcomes were assessed using Kaplan–Meier survival analysis with propensity score matching. We compared two transplantation cohorts (2000–2010 and 2011–2021) to assess potential changes in malignancy incidence, graft survival, and patient mortality.ResultsA total of 184,267 kidney transplantation recipients were included. Compared to the general population, transplantation recipients exhibited a higher risk of malignancy [standardized incidence ratio (SIR) 1.635; 95% confidence interval (CI), 1.600–1.670] and mortality [hazard ratio (HR) 1.115; 95% CI, 1.071–1.763; P < 0.0001]. The overall incidence of post-transplantation malignancies remained stable over the past two decades. Significant reductions in graft failure (HR 0.442; 95% CI, 0.413–0.473; P < 0.0001) and all-cause mortality (HR 0.755; 95% CI, 0.713–0.801; P < 0.0001) were observed in the recent decade.ConclusionKidney transplantation recipients remain at increased risk for malignancies and associated mortality. While the incidence of malignancies has not changed significantly over the past two decades, both graft failure and mortality have declined in the recent decade, potentially reflecting improvements in post-transplantation care and cancer management.